2020
DOI: 10.1111/sji.12945
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge on autoantigens and autoantibodies in psoriasis

Abstract: Psoriasis is a chronic inflammatory disease of the skin, with clinically characteristic erythematous and thick scaling plaques. 1 It is now well acknowledged that in addition to psoriatic arthritis (PsA), other comorbidities such as metabolic syndrome, cardiovascular diseases, gastrointestinal diseases, psychosocial disorders, infections and malignancies may accompany psoriasis. 2 They appear to result from environmental (e.g., infection or skin trauma) and genetic factors as well as enhanced levels of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Keratinocytes trigger psoriatic inflammation by producing autoantigens—including cathelicidin (LL-37), a disintegrin and metalloprotease domain containing thrombospondin type 1 motif-like 5, the neolipids associated with phospholipase A2 group IVD (PLA2G4D), and Keratin 17 [ 66 ]. Keratinocytes, additionally, facilitate DC autoantigen recognition by producing polyamines which prevent degradation of autoantigenic RNA [ 67 ].…”
Section: Barrier Aberration In Psoriasismentioning
confidence: 99%
“…Keratinocytes trigger psoriatic inflammation by producing autoantigens—including cathelicidin (LL-37), a disintegrin and metalloprotease domain containing thrombospondin type 1 motif-like 5, the neolipids associated with phospholipase A2 group IVD (PLA2G4D), and Keratin 17 [ 66 ]. Keratinocytes, additionally, facilitate DC autoantigen recognition by producing polyamines which prevent degradation of autoantigenic RNA [ 67 ].…”
Section: Barrier Aberration In Psoriasismentioning
confidence: 99%
“…The most studied autoantigen is cathelicidin antimicrobial peptide, also known as LL-37, which is produced by immune cells and keratinocytes in response to skin injury ( Figure 1 ). 11 , 12 LL-37 forms complexes with self-DNA or RNA that activates plasmacytoid DCs (pDCs) through Toll-like receptor-9 (TLR-9) and TLR-7, respectively. 13 , 14 Subsequently, the pDCs produce interferon (IFN)-α that activates conventional DCs (cDCs).…”
Section: Pathogenesismentioning
confidence: 99%
“…( Mahil et al, 2017 ) The findings demonstrated the enhanced expression of PLA2G4D in psoriatic epidermis , which was comparable to normal skin and eczematous lesions. ( Ten Bergen et al, 2020 ) Besides, mast cells, as one of the immune cells, were the main cell source of PLA2G4D, so it was not difficult to speculate the relationship between PLA2G4D and immune diseases. IL-36 could upregulate phospholipase PLA2G4D, which generated lipid antigen-presenting CD1A reactive T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…IL-36 could upregulate phospholipase PLA2G4D, which generated lipid antigen-presenting CD1A reactive T lymphocytes. Stimulation of this cell led to the production of IL-17 and IL-22 ( Ten Bergen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%